Antibiotics in surgery: its importance - Choice - Mechanisms of action - Fischer, Tabaré Mario (Cirugía del Uruguay, 1972)
The advent of chemotherapy and antibiotics in the third and fourth decades of this century not only modified the thematic pattern of infection but also had an fundamental on the pathology, the clinic and the whole social field. Hence, one must speak of an antibiotic era.